The Influence of Alexithymia and Childhood Trauma on Fear of Intimacy among Emerging Adulthood in Jabodetabek - Mutiara Annisa; Farhanah Murniasih (LPPM Universitas 17 Agustus 1945 Samarinda, 2026)
Fear of intimacy is a condition in which individuals experience a fear of emotionally opening up in close relationships, particularly among those in emerging adulthood. This study aims to examine the influence of alexithymia (difficulty identifying feelings, difficulty describing feelings, externally oriented thinking) and childhood trauma (physical abuse, emotional abuse, sexual abuse, physical neglect, emotional neglect) on fear of intimacy among emerging adults aged 18–25 years in the Jabodetabek area. The sample consisted of 210 respondents selected using a non-probability sampling technique with purposive sampling. The instruments used include the Fear of Intimacy Scale (FIS-35), Toronto Alexithymia Scale (TAS-20), and Childhood Trauma Questionnaire (CTQ-SF). Data analysis was conducted using Confirmatory Factor Analysis (CFA) to test construct validity and multiple regression analysis to examine the research hypotheses. The results indicate that alexithymia and childhood trauma simultaneously have a significant effect on fear of intimacy, contributing 15.2% of the variance. However, only the dimension of difficulty describing feelings showed a significant individual effect on fear of intimacy (p < 0.05). These findings emphasize the importance of emotional expression skills in building intimate relationships. These findings provide implications for future studies regarding trauma screening and the exploration of other psychological variables.